Rift activity and sequence stratigraphy of the Oligocene Dongying Formation in the Nanpu Sag, eastern China: Implications for rift sequence stratigraphy in lacustrine basins. (3rd March 2019) - Chen, Liang; Ji, Hancheng; Zhang, Liang; Zhu, Yue; Fang, Zheng
Abstract : Rifting plays an important role in accommodation variations in rift basins. However, fluvial discharge as another important factor affecting lacustrine rift sequence stratigraphy is not well explored. In this work, seismic and well data are used to investigate the stratigraphic features, rift activity, and effect of fluvial discharge in the Nanpu Sag, Bohai Bay Basin. The syn‐rift deposition of the Dongying Formation (28.5–23.8 Ma) is divided into four sequences (SQ1, SQ2, SQ3, and SQ4), and the rift‐related subsidence rate along two parallel boundary faults is calculated. The results indicate that the rift activity weakens from SQ1 to SQ4 and that the two parallel boundary faults consist of a total of four fault segments. As the fault segmented, three propagation folds formed intrabasin highs on which the Beipu, Laoyemiao, and Gaoliu outlets developed. Well logs and 3D seismic data show that from SQ1 to SQ3, retrogradational stacking patterns occur in Beipu, Laoyemiao, and the hanging‐wall ramp, while progradational stacking patterns occur in the Gaoliu outlet. In SQ4, the sequence stacking patterns are progradation‐dominated. By evaluating channel erosion and sediment supply, the fluvial discharge can be estimated, and the result indicates that the Gaoliu outlet has the strongest fluvial discharge from SQ1 to SQ3 with strong channel erosion, and in SQ4, the fluvial discharge of each outlet is comparable and relatively low. The high fluvial discharge of the Gaoliu outlet from SQ1 to SQ3 is considered to be the primary reason for the lake level rise in the intervals between the pulses of rift activities. Sequence stacking patterns and depositional trends in our study intervals are not in line with the rift subsidence rate; this indicates that rifting is not the only factor controlling the rift sequence stratigraphy and variations in the accommodation of lacustrine rift basins. While the Gaoliu outlet has predominant fluvial discharge from SQ1 to SQ3, progradational parasequence sets deposit in the Gaoliu outlet. In contrast, the retrogradational parasequence sets occurred in the Beipu outlet, Laoyemiao outlet, and the hanging‐wall ramp. As the fluvial discharge of the Gaoliu outlet decreased in SQ4, the fluvial discharge in each outlet became low, and the stacking patterns were dominated by progradation. Consequently, this research suggests that fluvial discharge is a significant factor controlling the accommodation creation in lacustrine rift basins, and a sequence model which gives a full consideration of fluvial discharge is constructed for lacustrine rift basins.